Multi-centre evaluation of the speed-oligo Mycobacteria assay for differentiation of Mycobacterium spp. in clinical isolates - Hofmann-Thiel Sabine; Turaev Laziz; Alnour Tarig; Drath Lore; Müllerova Maria; Hoffmann Harald (BMC Infectious Diseases, 2011)
Abstract Background A new DNA line probe assay (Speed-oligo Mycobacteria, Vircell) has been launched for rapid differentiation of Mycobacterium spp. from cultures. Compared to other line-probe assays, Speed-oligo Mycobacteria covers a relatively limited spectrum of species but uses a simpler and faster dip-stick technique. The present multi-centre, multi-country study aimed at evaluating the utility and usability of Speed-oligo Mycobacteria in routine mycobacteriology diagnostics. Results from Speed-oligo Myobacteria were compared to those from Genotype CM (HAIN lifescience, Nehren, Germany), another line-probe assay. Methods Speed-oligo Mycobacteria assay was performed in three main steps: 1) DNA extraction from cultured material 2) PCR amplification of the target gene and an internal control and 3) hybridization of the PCR products to specific probes by means of a dip-stick. Results Two hundred forty-two clinical isolates were recovered from consecutive positive mycobacterial cultures at two German (IML Gauting, Bioscientia Ingelheim), one Czech (KLINLAB Prague), and at a Sudanese (Khartoum) laboratory. All Mycobacterium species covered by the assay were reliably recognized. The rate of false positive results was 1.2% and concerned only the species M. marinum and M. peregrinum. The identification rate, i.e. the proportion of isolates which was correctly differentiated to the level of species or complex by the assay, differed significantly among laboratories being 94.9%, 90.7%, and 75.0% at the study sites IML Gauting, KLINLAB Prague and Bioscientia Ingelheim, respectively. This difference was caused by different spectra of NTM species encountered by the laboratory centres in daily routine diagnostics. Conclusions Speed-oligo Mycobacteria assay was proved a rapid and easy-to-perform alternative to conventional line-probe assays. The assay showed excellent sensitivity with regard to identification of genus Mycobacterium and species/complexes covered by the test. However, due to its relatively limited spectrum of taxa, a varying proportion of NTM may not be identified by the assay in daily diagnostics demanding further analyses. The only significant shortcoming in terms of specificity was the misidentification of the clinically relevant species M. marinum.